2015
DOI: 10.1539/joh.14-0028-oa
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions and leisure‐time physical activity among waged workers in South Korea: A cross‐sectional study

Abstract: Working conditions and leisure-time physical activity among waged workers in South Korea: A cross-sectional study: Chungah KIM, et al. School of Public Health, Seoul National University, Republic of Korea-Objectives: Although waged workers' working conditions have notably diversified in South Korea, there is little research addressing this issue. This study explores the relationship between working conditions and engagement in leisure-time physical activities (LTPA) among waged workers in South Korea. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
(34 reference statements)
1
11
0
1
Order By: Relevance
“…No age or sex differences were found for work factor changes and concurrent LTPA changes. The absence of sex differences is in agreement with other studies related to work hours,6 15 shift work17 40 and physical exertion 40. Sex differences have been more pronounced when work factors were combined in measuring job strain, although associations were also weak or inconsistent 41 42.…”
Section: Discussionsupporting
confidence: 91%
“…No age or sex differences were found for work factor changes and concurrent LTPA changes. The absence of sex differences is in agreement with other studies related to work hours,6 15 shift work17 40 and physical exertion 40. Sex differences have been more pronounced when work factors were combined in measuring job strain, although associations were also weak or inconsistent 41 42.…”
Section: Discussionsupporting
confidence: 91%
“…Many factors influence participatory behavior and motivation to participate in recreational sports, including demographic characteristics, such as gender, age, educational attainment, and socioeconomic status [7, 8]. Job characteristics, such as job control, working hours, and job security, also affect the frequency and willingness to spend time on leisure activities [9, 10]. Certainly, one's health status is also influential.…”
Section: Introductionmentioning
confidence: 99%
“…Shift work is defined as a job schedule in which working hours are outside of the standard daytime hours 1). In Korea, the number of shift workers is steadily growing,2) and a recent survey reported that approximately 10.9% of employees are shift workers 3)…”
Section: Introductionmentioning
confidence: 99%